Early Parenting Interactions and First-Time Mothers' Postnatal Depression and Parental Competence - Rachel W. E. Leong; Davinder Gill; Joanna Barlas; Patrick K. F. Lin (MDPI AG, 2024)
Objectives: Schema Therapy, an approach that integrates cognitive-behavioural and attachment principles, helps us understand the impact of early interactions with caregivers on adult mental health. These early interactions can be assessed through Schema Therapy-informed tools; however, these tools have yet to be used with a postnatal population, which represents a period of vulnerability for new mothers. Therefore, the present study aimed to evaluate the impact of positive and negative early parenting interactions on a first-time mother's mental health and her sense of competence during the postnatal period, using recently revised and newly developed Schema Therapy-informed tools. Design: This is a cross-sectional study. Method: First-time mothers (N = 220) participated in an online survey within 12 months post-birth. Participants completed the Positive Parenting Schema Inventory (PPSI), Young Parenting Inventory-Revised (YPI-R2), Edinburgh Postnatal Depression Scale (EPDS), and Parenting Sense of Competence (PSOC) scale. The data were analysed using hierarchical multiple regression and mediational analysis. Results: Negative early interactions with mothers and fathers led to greater postnatal depressive symptomology, while positive early interactions with mothers led to fewer postnatal depressive symptoms. Mediation analyses revealed that postnatal depressive symptoms mediated early parenting interactions and participants' sense of parenting competence as a new mother. Conclusions: The protective effects of positive early interactions with caregivers can help first-time mothers' postnatal emotional adjustment and their sense of competence through diminished postnatal depressive symptoms. However, the enduring effects of negative early interactions with caregivers can contribute to a first-time mother's risk of developing postnatal depression and negatively affect her sense of parental competence.